2018
DOI: 10.3390/ma12010109
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Textured Surfaces on Aluminum-Alloy Substrates

Abstract: The ways of producing porous-like textured surfaces with chemical etching on aluminum-alloy substrates were studied. The most appropriate etchants, their combination, temperature, and etching time period were explored. The influence of a specifically textured surface on adhesive joints’ strength or superhydrophobic properties was evaluated. The samples were examined with scanning electron microscopy, profilometry, atomic force microscopy, goniometry, and tensile testing. It was found that, with the multistep e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…The surface modifications should inhibit oxidation, promote adhesion of further coatings, or reduce staining. Wet chemical etching enables production of porous textured surfaces of aluminum-alloys [11]. Not only an appropriate combination of chemicals but the order of their applications is crucial to prepare porous surfaces, irrespective from the original roughness.…”
Section: This Special Issuementioning
confidence: 99%
“…The surface modifications should inhibit oxidation, promote adhesion of further coatings, or reduce staining. Wet chemical etching enables production of porous textured surfaces of aluminum-alloys [11]. Not only an appropriate combination of chemicals but the order of their applications is crucial to prepare porous surfaces, irrespective from the original roughness.…”
Section: This Special Issuementioning
confidence: 99%
“…Aluminum alloy has many uses for front and functional surfaces, which come into contact with other materials and weather conditions, therefore processes for its surface treatment have become a critical issue in research works. Kadleckova and co-workers [2] reported that with the multistep etching process, the aluminumalloy substrate can be effectively modified and textured to the same morphology, regardless of the initial surface roughness. In [3] the authors investigated the effects of surface roughness on the tribological properties of a textured surface.…”
Section: Introductionmentioning
confidence: 99%
“…In general, super-hydrophobic surface has water contact angle (WCA) larger than 150 • and water sliding angle (WSA) below 10 • , which is regarded as nearly perfect non-wetting [28]. Due to their special wetting properties, super-hydrophobic surfaces have been widely investigated in broad potential applications, such as anti-corrosion [29][30][31][32][33][34], anti-fouling [35,36], anti-icing [37,38], self-cleaning [27,39,40], oil-water separation [41,42], energy conversion [43], and catalysis [44]. Especially, the unique water repellency property of super-hydrophobic surfaces makes them practical to serve as an effective barrier to prevent the engineering materials underneath from further corrosion.…”
Section: Introductionmentioning
confidence: 99%